(Reading) Originality of the Concept in Arab Culture - an Anthropological Linguistic Study - (Islamic Sciences Journal, 2023)
This study seeks to confirm the originality of the concept of reading, its longevity, continuity and semantic richness in Arab culture, because the concept of reading is one of the most widespread concepts in our contemporary world as this concept is characterized by its richness, openness and complexity, so it was embraced by many scientific fields in its conceptual system as well as their use in extensive metaphorical connotations, in order to understand them, require a grasp of the roots and contexts of their use.The study stands on the root of the concept of reading in the Arabic lexicon and a brief pause through which it shows its positional load and how its sensory significance tops the load of the lexical material, followed by other semantics belonging to sensory areas lighter than it until it gets complicated little by little while it is on its way to abstraction .Then the study stops at the concept of reading in contemporary literature and trying to find a common content between the predicates of the lexical material and between what the idiomatic concept pulses in the contemporary world, in order to explain the semantic absorptive content of the subject matter which softens the complexity of what the terminological concept has ended in contemporary literature on its openness and bifurcation and complexity